APAKAH ADA HUBUNGAN ANTARA KUALITAS TIDUR DENGAN FUNGSI KOGNITIF LANSIA? - Raden Siti Maryam; Ruth Teresna Silitonga; Ni Made Riasmini; Mia Fatma Ekasari; Puspita Hanggit Lestari (PT Nuansa Fajar Cemerlang, 2026)
Background: The elderly life stage is characterized by increased vulnerability to decline in physiological and psychological functions, including sleep quality and cognitive function. Sleep disorders in the elderly can be fatal, one of the impacts is decreased cognitive function. Objective: This study aims to examine the relationship between sleep quality and cognitive function in the elderly in the Posyandu Melati area, RW.09, East Jakarta. Research Method: This study used a cross-sectional design with a quantitative approach. A total of 106 elderly were selected by purposive sampling. The instruments used included the Pittsburgh Sleep Quality Index (PSQI) to assess sleep quality and the Indonesian version of the Montreal Cognitive Assessment (MoCA-Ina) to measure cognitive function. Data were analyzed using the Chi-Square test. Results: The findings showed that the majority of respondents had poor sleep quality (58.5%) and abnormal cognitive function (88.7%). There was a relationship between age and education level with cognitive function (p = 0.026 and 0.003). There was a significant relationship between sleep quality and cognitive function in the elderly (p = 0.001). Conclusion: Elderly with poor sleep quality are 20 times more likely to experience cognitive impairment. These findings highlight the importance of addressing sleep quality in older adults as a means of maintaining cognitive function. Nurses play a crucial role in providing education and interventions to improve sleep quality in older adults to prevent cognitive decline through Integrated Primary Care Posyandu (Posyandu ILP) activities and community group activities.